Study of the combined radial post-feeding dispersion of the blowflies Chrysomya megacephala (Fabricius) and C. albiceps (Wiedemann) (Diptera, Calliphoridae) - Gomes, Leonardo [UNESP]; Von Zuben, Claudio José [UNESP] (Sociedade Brasileira de Entomologia, 2005)
As moscas- varejeiras utilizam-se de substratos discretos e efêmeros para alimentar suas larvas. Após deixarem o substrato alimentar, as larvas começam a dispersar em busca de locais adequados para pupação e fontes adicionais de alimento, um processo denominado dispersão larval pós-alimentar. Alguns aspectos importantes desse processo foram estudados em uma arena permitindo a dispersão radial combinada de larvas de C. megacephala e C. albiceps. Para determinar a localização de cada pupa, a arena foi dividida em 72 setores iguais começando do centro. A distância a partir do centro, a profundidade e o peso de cada pupa foram determinados. Testes estatísticos foram feitos para verificar a relação entre peso, profundidade e distância para pupação. de um total em média de 976 larvas soltas (488 de cada espécie) foram coletadas considerando ambos os experimentos 456 larvas de C. megacephala e 488 larvas de C. albiceps. Isso demonstrou que as larvas de C. albiceps provavelmente predaram 32 larvas de C. megacephala. O estudo desse processo de dispersão pode auxiliar na estimativa do intervalo pós- morte (IPM) em estudos de medicina legal.

Blowflies use discrete and ephemeral substrates to feed their larvae. After they run out of food, the larvae begin to disperse in order to find adequate places for pupation or additional food sources, a process named post-feeding larval dispersion. Some important aspects of this process were studied in a circular arena allowing the combined radial post-feeding dispersion from the center of the arena of C. albiceps and C. megacephala larvae. To determine the location of each pupa, the arena was divided in 72 identical sections starting from the center. The distance from the center, the depth and weight of each pupa were evaluated. Statistical tests were done to verify the relation between weight, depth and distance for pupation. From the total an average of 976 larvae released (488 for each species) were collected considering both experiments 456 C. megacephala pupae and 488 of C. albiceps. This demonstrates that C. albiceps probably preyed on 32 C. megacephala larvae during post-feeding dispersion. The study of this dispersion process can be used to estimate the postmortem interval (PMI) of human cadavers in legal medicine.
Estudo da dispersão radial combinada de Chrysomya megacephala (Fabricius) e C. albiceps (Wiedemann) (Diptera, Calliphoridae)
Keywords: Calliphoridae; C. albiceps; C. megacephala; dispersão; entomologia forense; Calliphoridae; C. albiceps; C. megacephala; dispersion; forensic entomology